Peri-implant bone level assessment of early loaded dental implants submitted to different prosthetic protocols: a case report - Yoshiyasu, Rodrigo Hideki (2023)
Aim: The present split-mouth case report aims to describe the clinical and radiographic long-term outcomes ofthe implant rehabilitation of two mandibular premolars in which the digital workflow was used to apply differentprosthetic protocols. Case description: A female 42-year-old patient with the absence of both mandibular secondpremolars was submitted to guided surgery for the placement of platform-switching Grand Morse connectionimplants. Digital workflow was used for implant and prosthetic planning, applying early loading protocol 21 daysafter surgery. The implant on the right side received the final abutment at the time of surgery (without loading),whereas the implant on the left side had a healing abutment placed, which was replaced by a temporary abutmentand then by a final abutment. Two months after surgery, both implants had final ceramic restorations delivered.The patient was followed clinically and radiographically for 30 months, presenting excellent hard and soft tissueoutcomes, with bone level changes lower than 2mm for both implants. Conclusion: The use of digital workflowand early loading, made the present implant-supported rehabilitation predictable, safe and time-efficient, resultingin total patient satisfaction. Peri-implant bone level was observed to be stable after early loading protocol forboth platform-switching connection implants inserted, despite the prosthetic protocol applied.KEYWORDSDental implants; Prosthesis; Computer-aided design; Platform-switching; Bone loss; Patient satisfaction.